Analysis of The Effect of Work Stress and Work Environment On Employee Performance (Case Study In PT Indofood CBP Sukses Makmur, Tbk Plant Tanjung Api-Api Palembang) - Yulianti, Yeni; Perizade, Badia; Zunaidah, Zunaidah (Devotion : Journal of Research and Community Service, 2022)
The purpose of this study was to obtain empirical evidence by analyzing the effect of work stress and work environment on employee performance at PT Indofood CBP Sukses Makmur, Tbk Plant Tanjung Api-api Palembang. The sample in this study were employees of PT Indofood CBP Sukses Makmur, Tbk Plant Tanjung Api-Api Palembang with a population of 169 people. The sampling technique in this study was random sampling as many as 119 respondents. The analysis technique used is multiple linear regression analysis. The results of this study indicate that 1) work stress has a positive and significant effect on employee performance; 2) The work environment has a positive and significant effect on employee performance at PT Indofood CBP Sukses Makmur, Tbk Plant Tanjung Api-Api Palembang. Suggestions that can be submitted include 1) Need to evaluate in providing a workload that is in accordance with the jobdesk and responsibilities; 2) It is necessary to renew the room arrangement for the convenience of being in the workspace; 3) It is necessary to evaluate the addition of the number of human resources to reduce high stress due to workloads that exceed responsibilities